2011
DOI: 10.7205/milmed-d-10-00196
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Musculoskeletal Injuries Among Greek Army Officer Cadets During Basic Combat Training

Abstract: Despite the absence of fractures and the low number of upper extremity injuries during the BCT, injury prevalence was high, with ankle- and foot-related injuries to be responsible for a long period of lost training days. Preventive efforts should focus on addressing the high rate of first-time and recurrent ankle ligament sprains and possible protective equipment to limit their frequency and severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 0 publications
4
23
0
3
Order By: Relevance
“…Previous studies reported the highest injury rates to occur within the first nine weeks of training with spikes at week 2 when physiological stress was considered greatest [8,9,48]. Similar observations were made by Almeida et al [49] and more recently by Havenetidis et al [50] where as much as 51.3% of training injuries were reported in the first two weeks of initial military training. It is proposed that the reduced incidence and spikes during the initial weeks of training is in part a result of the OMEGA programme which was specifically designed to progressively condition the recruits such to avoid a mismatch in physical capacity and applied load.…”
Section: Week Of Injurysupporting
confidence: 73%
“…Previous studies reported the highest injury rates to occur within the first nine weeks of training with spikes at week 2 when physiological stress was considered greatest [8,9,48]. Similar observations were made by Almeida et al [49] and more recently by Havenetidis et al [50] where as much as 51.3% of training injuries were reported in the first two weeks of initial military training. It is proposed that the reduced incidence and spikes during the initial weeks of training is in part a result of the OMEGA programme which was specifically designed to progressively condition the recruits such to avoid a mismatch in physical capacity and applied load.…”
Section: Week Of Injurysupporting
confidence: 73%
“…The lower limbs in particular have been found to be the leading site of injury to military populations not on combat operations [28][29][30]. In some instances, injuries to the lower limbs have represented over 80% of reported injuries in a military population [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that large and rapid increases in physical activity in military training with the associated psychological challenges can lead to MSKI 1 2 6 7 13 14 18. Military recruits are known to be at a higher risk of injury compared with trained soldiers 19. The lack of appropriate conditioning and preparation for increasing the intensity of training may be considered as a fault which in turn may contribute to greater incidence of potentially avoidable injury 1 8 15…”
Section: Introductionmentioning
confidence: 99%